Pengaruh Disiplin Kerja, Motivasi dan Kompetensi Terhadap Kepuasan Kerja Karyawan PT. Bank Syariah Indonesia (BSI) Di Kcp Buah Batu 2 - Alamsah, Dilan; Siddiq, Andhika Mochamad (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the influence of Work Discipline, Motivation, and Competence on Job Satisfaction at Bank BSI Buah Batu 2 using a quantitative research method with a verificative and descriptive analytical approach. The primary data was collected through pre-surveys, questionnaires, document collection, and interviews with employees of BSI Buah Batu 2. The research sample was selected using a non-probability sampling method, specifically the judgment sampling technique, resulting in a total of 31 employees as both the population and sample of the study. Regression analysis results indicate that Work Discipline, Motivation, and Competence significantly influence Job Satisfaction. The coefficient of determination shows a value of 0.795 or 79.5%, meaning that overall, the variables of Work Discipline, Motivation, and Competence simultaneously influence Job Satisfaction, contributing 79.5%, while the remaining 20.5% is influenced by other factors.